Pertimbangan Dewan Syariah Nasional dalam Menetapkan Fatwa Akad Transaksi Syariah di Indonesia - M Ridhwan Ar Rasyid; Efri Syamsul Bahri (Universitas Muhammadiyah Sidoarjo, 2019)
The National Sharia Council of the Indonesian Ulema Council (DSN MUI) is an independent institution that plays a role in providing sharia lawyer arrangements. DSN MUI makes a fatwa to regulate the process of asset turnover in community life. DSN MUI formulates the consideration of fatwa akad sharia transaction using the concept of scientific method based on the guidance of fiqh scholars. This study aims to describe the consideration of DSN MUI in determining the fatwa of sharia transaction contracts. Based on this study, the consideration of fatwa akad Islamic transactions aims to benefit the people using the concept of nash qath'i approach refers to Al-Qur'an and Al-Hadist. Consideration in determining fatwas based on benefits and impacts that will occur when a fatwa is determined or not determined.